The effects of water temperature on weight and length growth in Bester - Baradaran Noveiri, S.; Chakmehduz Ghasemi, F.; Mohammadi Parashkuh, H.; Abbasalizadeh, A.; Mohseni, M.; Bahmani, M.; Efatpanah Komaii, I.; Pourali Fashtomi, H.R.; Alipour, A.; Yarmohammadi, M.; Darvishi, S. (2010)
Hybrid Bester sturgeon (female Beluga x male Sterlet) was produced for the first time in Iran using sperm from a male Acipenser ruthenus and eggs of a female Huso huso in Shahid Marjani Sturgeon Porpagation Center (Agh Ghala, Golestan province). Bester fries and those of Beluga as control treatment weighed 490mg and 377mg respectively after about one month and were transported to International Sturgeon Research Institute (Rasht). All fishes were fed by artificial concentrated food (48-50% protein and 1547% fat) after a period of feeding on Artemia and Daphnia. Sorting was carried out according to weight increase for both fishes. Results showed that the weight increase in warmer months (water temperature 18-28°C) was higher than the colder months and ceased at 6-12°C. The trend in weight increase was of the same pattern for both fishes. There were no significant differences between fish length up to 5 months of rearing but afterwards, Bester showed a higher rate of length increase compared to that of the Beluga. The length increase rate for both fishes was sharper during the first year than the second year. Fish length increase was ceased at 6.841.4°C which coincided with the increase in fish weight.